MODIFYING THE TRADITION OF PRAYING FOR THE DEAD: STUDY OF LIVING HADITH - Kasman (Al'Adalah, 2022)
Muhammadiyah people are not used to carrying out the Javanese Muslim slametan tradition of praying for the dead. Muhammadiyah members in Cakru Village, Kencong Jember East Java, still carry it out. This article discusses the slametan tradition of praying for the dead, carried out by Muhammadiyah members—also called the recitation of dhikr al-mawt (remembering the death)—using phenomenological analysis. The forms and reasons for holding it and attending it are also discussed. This article focuses more on how Muhammadiyah members modify the tradition, such as reciting verses of the Qur’an without tawassul (intercession of prayer by relying on the prophet and ulama to get closer to God) or recitation with tawassul before reading Surah Yasin and Tahlil. After that, tausiyah (preaching for giving wise advice and Islamic teaching to remember death), praying for the dead, and then a banquet (kenduri or berkat). However, they were forced to carry this Javanese tradition out for preaching (da'wah), praying for the dead, consoling the deceased’s family, and maintaining Muslim harmony, cohesiveness, and integrity.